OP0262 FACTORS ASSOCIATED WITH ACUTE ANTERIOR UVEITIS IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS: ANALYSIS OF THE BSRBR-AS REGISTER DATABASE. (June 2019) - Derakhshan, Mohammad H.; Dean, Linda; Jones, Gareth T.; Macfarlane, Gary J.; Siebert, Stefan; Gaffney, Karl
Abstract : Background: Acute anterior uveitis (AAU) is one of the key extra-articular manifestations in axial spondyloarthritis (axSpA). The presence of AAU may influence the decision to start and the choice of biological therapy. Objectives: To examine the factors associated with AAU in patients with axSpA in the British Society for Rheumatology Biologics Register in Ankylosing Spondylitis (BSRBR-AS). Methods: Clinical and patients-reported outcomes of 2420 patients with axSpA from 83 rheumatology centres in the United Kingdom were collected as part of the BSRBR-AS. Patients with AAU diagnosed by an ophthalmologist were compared to those without AAU in relation to demographic and lifestyle factors. The associations were analysed using univariable and multivariable logistic regression models, considering necessary interaction terms and sensitivity analyses. Results: 568 (23.5%) patients in the cohort had at least one episode of AAU. The male/female ratio was 2.0:1 and group's median (IQR) age was 51 (41 – 61) years. Factors associated with higher odds of AAU in univariable analyses were HLA-B27 positivity [OR 2.32 (95%CI: 1.66 – 3.23)], university degree [OR 1.44 (95%CI: 1.53 – 1.79)], age [OR (per year) 1.02 (95%CI: 1.01 – 1.03)] and axSpA disease duration [OR (per year) 1.02 (95%CI: 1.02 – 1.03)]. Ever-smoking was inversely associated with AAU [(OR 0.71 (95%CI: 0.59 – 0.89)]. Ever-alcohol drinking (p=0.213), BMI (p=0.325) and gender (p=0.317) did not show any associations. In multivariable analysis, the magnitude of associations remained significant for HLA-B27 positivity, age, and axSpA disease duration, as did the inverse association with smoking (see Table). Analysis restricted to patients with inflammatory bowel disease did not alter the relationship between AAU and the above risk factors. Conclusion: The odds of having a diagnosis of AAU is high in axSpA patients with positive HLA-B27, and longer disease duration (having controlled for age). The negative association with smoking in this large cohort contrasts with previous published data and warrants further evaluation. Acknowledgement: British Society of Rheumatology Disclosure of Interests: Mohammad H. Derakhshan: None declared, Linda Dean: None declared, Gareth T. Jones Grant/research support from: Have received research grants (not current) from Abbvie and Pfizer. Have received research grants (not current) from the British Society for Rheumatology, who received the funds from Abbive, Pfizer and UCB. Have received research grant (current) from the British Society for Rheumatology, who received the funds from Celgene., Gary J. Macfarlane Grant/research support from: Have received research grants (not current) from Abbvie and Pfizer. Have received research grants (not current) from the British Society for Rheumatology, who received the funds from Abbive, Pfizer and UCB. Have received research grant (current) from the British Society for Rheumatology, who received the funds from Celgene., Stefan Siebert Grant/research support from: AbbVie, Novartis, Pfizer, Janssen, BMS, Celgene, UCB, and Boehringer Ingelheim, Consultant for: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, Speakers bureau: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, Karl Gaffney Grant/research support from: Abbvie, Pfizer, Consultant for: Abbvie, Lilly, Novartis, UCB, Speakers bureau: Abbvie, Biogen, Gilead, Lilly, Novartis, UCB